Sistem Pendukung Keputusan Pemilihan Jenis Investasi Menggunakan Metode Analytical Hierarchy Process (AHP) - Fauzi, Muhammad; Vikri, Muhammad Jauhar; Wahyudhi, Sunu (Al-Mantiq, 2024)
Currently, the investment sector is experiencing rapid development in Indonesia. However, the lack of understanding of how to choose the optimal investment results in less accurate and appropriate decision making, which in turn can result in losses in making investments. The purpose of the investment type selection decision support system is to provide convenience to new investors in making decisions regarding the type of investment. Dataxcollection is done by interview, observationcand literature study. Fromxthe results of data collection, several alternatives were obtained, namely stocks, mutual funds, bonds and deposits with selection criteria including risk, return and liquidity. Data processing is done with one of the DSS (Decision Support Systems) methods, namely the AnalyticalxHierarchy Process (AHP) method, with the results of stocks being determined as the best investment option.